2016
DOI: 10.5194/isprsarchives-xli-b1-1127-2016
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Assessment of Coastal Topography Derived From Uav Images

Abstract: To monitor coastal environments, Unmanned Aerial Vehicle (UAV) is a low-cost and easy to use solution to enable data acquisition with high temporal frequency and spatial resolution. Compared to Light Detection And Ranging (LiDAR) or Terrestrial Laser Scanning (TLS), this solution produces Digital Surface Model (DSM) with a similar accuracy. To evaluate the DSM accuracy on a coastal environment, a campaign was carried out with a flying wing (eBee) combined with a digital camera. Using the Photoscan software and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…2012; Long et al. 2016), and producing a high accuracy (>70%) in object‐based classification (Rau et al. 2012).…”
Section: Introductionmentioning
confidence: 99%
“…2012; Long et al. 2016), and producing a high accuracy (>70%) in object‐based classification (Rau et al. 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that computing resources, software, data, and algorithms are fully capable of analyzing a large volume of data at multiple spatial scales to derive an understanding of the complex changes and the interplay among the various coastal processes at work in this area. Future research could build upon this multi-scale approach by using imagery obtained from unmanned aerial systems (UASs) at a very local scale where land cover and shoreline changes have been identified [41][42][43][44][45]. Instrumentation aboard unmanned aerial vehicles (UAVs) can provide excellent spatial resolution as well as multispectral bands; however, the coverage is limited because of battery time for overflights and access to launch and retrieve equipment can be problematic [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Future work could test the classification of barrier island geomorphology using unmanned aerial vehicle (UAV) imagery; however, a digital terrain model (DTM) is not equivalent to a DEM and therefore fieldwork should be conducted to correctly calibrate UAV imagery [37][38][39]. The areas mapped in this study have plenty of Lidar data; however, this is not always the case and so UAV imagery may be a useful alternative.…”
Section: Discussionmentioning
confidence: 99%